Handling Access to Agrarian Reform After Legalization of Assets in Cilacap Regency (The Relationship between Access to Agrarian Reform and Community Motivation in Utilizing Land Certificates) - Millenda, Rizky Nauval; Setiowati, Setiowati (Sekolah Tinggi Pertanahan Nasional, 2024)
Agrarian Reform is a major agenda of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency mandated by TAP MPR IX/MPR/2001 concerning Agrarian Reform and Natural Resources Management. TAP MPR IX/MPR/2001 Article 2 highlights two primary facets of agrarian reform: the ownership and control (land reform) aspect and the use and utilization aspect. Asset structuring, through asset legalization, implements the ownership and control (land reform) aspect. We implement aspects of land use and utilization through access arrangement activities. We have implemented asset structuring activities intensively. On the other hand, access handling activities have not been implemented optimally. The Cilacap Regency Land Office has designated Sidamukti Village, Patimuan District, Cilacap Regency as the location for the 2022 Cilacap Regency Land Office's Agrarian Reform Access Handling activity. This activity builds on the asset structuring activities conducted through PTSL in 2021. Research on Handling Access We conducted a quantitative study using the Sperm Correlation Test following the legalization of assets in Sidamukti Village, Patimuan District, Cilacap Regency. The study's findings demonstrate that we followed the Technical Guidelines for Handling Access to Agrarian Reform in 2022 when managing access to agrarian reform. There exists a correlation between the implementation of agrarian reform access management and the community's motivation to utilize land certificates. Additionally, a correlation exists between the community's proficiency in information and production technology, specifically in entrepreneurship, and their utilization of land certificates following asset validation.